Cationic cobalt-catalyzed [1,3]-rearrangement of N-alkoxycarbonyloxyanilines - Nakamura, Itaru; Owada, Mao; Jo, Takeru; Terada, Masahiro (Beilstein Journal of Organic Chemistry, 2018)
A cationic cobalt catalyst efficiently promoted the reaction of N-alkoxycarbonyloxyanilines at 30 °C, affording the corresponding ortho-aminophenols in good to high yields. As reported previously, our mechanistic studies including oxygen-18 labelling experiments indicate that the rearrangement of the alkoxycarbonyloxy group proceeds in [1,3]-manner. In this article, we discuss the overall picture of the cobalt-catalysed [1,3]-rearrangement reaction including details of the reaction conditions and substrate scope.
Keywords: anilines; cobalt catalyst; concerted reaction; N–O bond; rearrangement